Application of seabuckthorn (Hippophae rhamnoides L.) leaf extract as antimicrobial finish on aramid fabric. (March 2016) - Yogendra Kumar, MS; Raghu, TS; Varghese, FV; Indu Shekar, R; Kotresh, TM; Rajendran, R; Murugesh Babu, K; Padaki, VC
In this study, we have extracted bioactive compounds from seabuckthorn (SBT) leaves. Total flavonoid content of SBT leaf extract estimated as rutin equivalent was found to be 116.98 ± 3.06 mg/g of extract. Further, we pre-treated aramid (Nomex IIIA) fabric with triethylene tetramine to increase the wickability of the fabric for better extract uptake. Surface etching on the amine treated fabric morphology was determined by scanning electron microscope analysis. Then, SBT leaf extract was coated using citric acid as cross-linking agent on to aramid fabric by pad-dry-cure method for improved wash durability. Universal attenuated total internal reflection Fourier transform infrared characterization of the SBT coated fabric showed distinct hydroxyl peak at 3305 cm −1, carbonyl peak at 1728 cm −1, and –C–O–C peak at 1083 cm −1 . There was no significant difference in the char produced by SBT coated fabric and control samples as estimated using flammability tester. Antimicrobial activity of the SBT coated fabric was assessed by both qualitative (agar diffusion method) and quantitative (percentage reduction test) methods using test organisms. An inhibition zone for Escherichia coli and Staphylococcus aureus was found to be 10.2 mm and 12.3 mm, respectively, by agar diffusion method. Quantitative assessment by percentage reduction test showed a reduction percentage of 96.00% and 93.00% for S. aureus and E . coli, respectively. Results suggested that SBT might be a valuable ingredient for the development of antimicrobial aramid textiles.